2003
DOI: 10.1029/2003ja010144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a large‐amplitude circularly polarized wave on linear beam‐plasma electromagnetic instabilities

Abstract: [1] In a previous paper, sufficiently large-amplitude and left-handed ''pump waves'' propagating parallel to the background magnetic field were shown to stabilize a moderately dense beam in a proton plasma against the generation of waves drawing their energy from the differential streaming motion of the beam [Gomberoff, 2003]. We now examine the general case of both left-hand and right-hand pump waves and their effects on beam instability as a function of pump wave amplitude and frequency, beam speed, and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Nonlinear ion‐acoustic like instabilities can occur in a system with one and two ion beams [ Gomberoff et al , 2003, 2004a, 2004b, 2005; Hoyos and Gomberoff , 2005; Gomberoff and Hoyos , 2005; Gomberoff , 2006a, 2006b, 2006c, 2007a]. In the presence of two ion beams, nonlinear ion‐acoustic like waves can be triggered by linear ion‐acoustic waves associated supported by the background plasma and by each one of the beams [ Gomberoff , 2007b].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonlinear ion‐acoustic like instabilities can occur in a system with one and two ion beams [ Gomberoff et al , 2003, 2004a, 2004b, 2005; Hoyos and Gomberoff , 2005; Gomberoff and Hoyos , 2005; Gomberoff , 2006a, 2006b, 2006c, 2007a]. In the presence of two ion beams, nonlinear ion‐acoustic like waves can be triggered by linear ion‐acoustic waves associated supported by the background plasma and by each one of the beams [ Gomberoff , 2007b].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of large amplitude waves in the solar wind has been invoked in order to account for some unresolved problems [ Gurnett et al , 1979; Kurth et al , 1979; Gurnett , 1991; Gomberoff et al , 2003; Araneda and Gomberoff , 2004; Kaghashvili et al , 2003, 2004; Gomberoff et al , 2005]. The fact that the stabilization properties of the magnetosonic instability in the presence of two beams can be different than that of the case of only one beam, can also help to understand such processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gomberoff 20,21 first carried out the linear analysis of ion beam instabilities in the presence of the finite amplitude circularly polarized Alfv en waves and demonstrated that the growth of the beam instabilities are stabilized. Later, the stabilization processes were numerically confirmed by numerical simulation by using onedimensional (1-D) hybrid code.…”
Section: Introductionmentioning
confidence: 99%